2015
DOI: 10.3923/mj.2015.28.35
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multidrug-Resistant (MDR) Salmonella enteritidis in Poultry and Backyard Chicken from Tiruchirappalli, India

Abstract: This study aimed to investigate the prevalence of multidrug resistant Salmonella enteritidis from poultry chicken in comparison with the backyard country chicken along with their seasonal variation in Tiruchirappalli, Tamilnadu, India. A total of 325 rectal swab samples of chicken were included for this study. Among them 157 and 168 were from poultry and backyard chicken, respectively. Samples were randomly collected during each season like monsoon, post monsoon, Winter and Summer from July 2010 to June 2011. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
(25 reference statements)
2
13
1
Order By: Relevance
“…The overall prevalence of Salmonella in the present study was 25.82%. These findings are in line with other researchers who have reported higher prevalence of Salmonellae in chilled chicken meat samples (51%) [ 24 ], CBF (32.5%), backyard chicken (21.4%) [ 25 ], CBF supply chain (14.52%) [ 26 ], poultry meat (8.18%) [ 27 ], and egg contents (0.5%) [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The overall prevalence of Salmonella in the present study was 25.82%. These findings are in line with other researchers who have reported higher prevalence of Salmonellae in chilled chicken meat samples (51%) [ 24 ], CBF (32.5%), backyard chicken (21.4%) [ 25 ], CBF supply chain (14.52%) [ 26 ], poultry meat (8.18%) [ 27 ], and egg contents (0.5%) [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study clearly indicate that there was higher AMR to tetracyclines, β -lactams, fluoroquinolones, aminoglycosides, polymyxin, ESBL inhibitors, folate pathway inhibitors, and less resistance to phenicols. Similar finding has been reported elsewhere for β -lactam and macrolide antibiotics (52.9-100%) [ 25 ] while lesser resistance to chloramphenicol (3.13%) and higher resistance to ciprofloxacin and β -lactams (68.75-100%), tetracycline (65.62%), and colistin sulphate (46.87%) were reported in other studies [ 42 ]. Previous researchers have reported that there was shift in antibiotics selection used for treatment of Salmonella infections in poultry, from chloramphenicol and ampicillin to trimethoprim-sulfamethoxazole, fluoroquinolones, and extended-spectrum cephalosporins [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 90%
“…The multi‐drug resistance also was higher in Salmonella enteritidis strains in poultry chicken compared to that of the backyard chicken in India (Bhuvaneswari et al . 2015). This trend has been attributed to the fact that in domestic settings and subsistence farming, there is less evidence of inappropriate antibiotic use in livestock (Rousham et al .…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, significantly higher levels of antibiotic resistance were found in Escherichia coli populations circulating in the poultry-farming production environment vs the domestic environment in rural Ecuador (Braykov et al 2016). The multi-drug resistance also was higher in Salmonella enteritidis strains in poultry chicken compared to that of the backyard chicken in India (Bhuvaneswari et al 2015). This trend has been attributed to the fact that in domestic settings and subsistence farming, there is less evidence of inappropriate antibiotic use in livestock (Rousham et al 2018).…”
Section: Antimicrobial Resistance and Pathogenic Potentialmentioning
confidence: 99%
“…Similarly, high prevalence of resistant Salmonella has been reported for chickens slaughtered in the outlets of the ‘wet market’ in other countries, such as in the cecal contents of chickens slaughtered in ‘pluck shops’ in Trinidad [ 46 ] where 100.0% of the Salmonella isolates were resistant to antimicrobial agents which included 10 of the 16 used in the current study and in India where 100.0% (51/51) of Salmonella isolates from the rectal swabs in poultry exhibited resistance to 16 antimicrobial agents [ 49 ].…”
Section: Discussionmentioning
confidence: 99%